Balanced biogeographic and local environmental effects determine the patterns of microbial diversity in biocrusts at multi-scales - Li, Yuanlong; Wang, Fengdi; Yang, Haijian; Li, Hua; Hu, Chunxiang (Frontiers in Microbiology, 2023)
Biodiversity maintenance and its underlying mechanisms are central issues of ecology.However, predicting the composition turnovers of microbial communities at multiple spatial scales remains greatly challenging because they are obscured by the inconsistent impacts of climatic and local edaphic conditions on the assembly process.Here, at a subcontinental scale of Northern China, we investigated soil bacterial and eukaryotic communities in biocrusts with different successional levels. Resultsshowed that irrespective of spatial scale, bacterial α diversity increased but eukaryotic diversity decreased with the primary succession, whereas both β diversities decreased at the subcontinental scale compared with smaller scales, indicating that the biogeographic pattern of soil microorganisms was balanced by successional convergence and distance decay effect. We found that the convergence of bacterial and eukaryotic communities was attributed to the turnovers of generalist and specialist species, respectively. In this process, edaphic and climatic factors showed unique roles in the changes of diversity at local/subcontinental scales. Moreover, the taxonomic diversity tended to be more susceptible to climatic and edaphic conditions, while biotic factors (photosynthesis and pigments) were more important to phylogenetic diversity. Taken together, our study provided comprehensive insights into understanding the pattern of microbial diversity at multiple spatial scales of drylands.